Graphene-reinforced silicon oxycarbide composites prepared by phase transfer. (November 2018) - Yu, Min; Picot, Olivier T.; Saunders, Theo G.; Dlouhý, Ivo; Feng, Jinyu; Titirici, Maria-Magdalena; Mahajan, Amit; Reece, Michael J.
Abstract: In order to compensate for cracking, brittleness and low electrical conductivity of polymer-derived silicon oxycarbide (SiOC), graphene was successfully introduced into a SiOC matrix by phase transfer of graphene oxide (GO) from an aqueous (GO dispersed in water) to organic phase (copolymer as SiOC precursor in diethyl ether). Spark plasma sintering (SPS) was used to fully densify composites to ∼2.3g/cm 3 . The prepared materials were comprehensively characterized and exhibited significant enhancement in the mechanical properties, electrical conductivity and electrochemical performance. Self-assembled lamellar structure of graphene in the SiOC-matrix was achieved, leading to anisotropy in the properties of the composites. The fracture toughness of the SiOC-2vol%GO composite was increased by ∼91%, at the expense of a slight decrease in the flexural strength, compared to the SiOC-matrix. Moreover, the composites exhibited three orders higher electrical conductivity than the SiOC-matrix. The electrical conductivity in the perpendicular direction (σ┴ = 3 × 10 −1 S/cm) of SiOC-2vol%GO composites was two orders of magnitude higher than that in the parallel direction (σ‖ = 4.7 × 10 −3 S/cm), owing to the self-assembled lamellar graphene in the SiOC-matrix. The SiOC-2vol%GO composites further showed better electrochemical performance of oxygen reduction reaction (ORR) than pure graphene, exhibiting an onset potential (∼0.75 V vs RHE) and more positive half-wave potential (∼0.6 V vs RHE). Graphical abstract: Image 1